PENCIPTAAN KARYA SENI PERTUNJUKAN BERBASIS SUSASTR A â€œDANG, LAMPUNG GHAM KARAMâ€ - Goesthy Ayu Mariana Devi Lestari (Gelar : Jurnal Seni Budaya, 2014)
â€œDang, Lampung Gham Karamâ€ is a title chosen to represent the whole content of this literary work of performingart. The terms come from Lampung language that means â€œJanganlah, Lampung Kita Karamâ€ (Donâ€™t be sunkour Lampung). Interpretation of a literary work â€œLampung Karamâ€ produces other idea in creating a workâ€œDang, Lampung Gham Karamâ€ that means the sink of Lampung physically at the time of Krakatau eruptionin 1883 doesnâ€™t make Lampung socially as well culturally sunk. The multi ethnics in Lampung have beenexisted since the natural event of Krakatau and getting more advanced to color the identity of Lampungnowadays. This work uses the element of traditional arts in Lampung culture that is potentially supported bythe physical empiric memory of creator. The cultural reaction between Lampung and other culture and alsothe various branches of arts (not only dance art) supports to enrich this work of art. The performance work ofart is not only supported by the various forms of dance but also the other art field covering the arts of music,literature, and the various traditional theater of Lampung. The work presentation is executed in a close as wellas open room. The change of performance place becomes the dynamics and color in the performance.Keywords: Krakatau, Lampung, sink, literature, performance